Comparison of right ventricular global longitudinal strain between pacemaker lead position in patients with permanent pacemaker - Muhamad Fakhri; Hauda El Rasyid; Mefri Yanni; Rizanda Machmud (The Indonesian Heart Association, 2026)
In “Comparison of right ventricular global longitudinal strain between pacemaker lead position in patients with permanent pacemaker” (Indonesian Journal of Cardiology, 46(2), 64-70. https://doi.org/10.30701/ijc.1592), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1592. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1592